Informação e Cidadania na Penitenciária e Presídio do Roger - Malaquias, Josinaldo José Fernandes (1999)
In face of the failure of the brazilian penitentiary sistem, characterized by the disrespect and violation of the human rights, we tried to analyse, on this study, the informational practices between the convicts from the Roger Prison and fail, in Joao Pessoa-PB, while (as) a modification element of the prisoners quotidian. We used as a tecnique of data collection a semi-structured interview and a questionary to a universe (whole) of 23 prisoners. Ten (10) attended the interviews and 13 answered the questionaries. Using the technique of the life history, linked to notions of content analysis, we proceded the data analysis. Subsidiarily we used journalistic matters from the following newspapers: 0 Norte and Correio da Paraiba, involving the penitentiary subject (question) in Paraiba. for us to compare them with the declarations of de convicts. We discovered that from the guiding principles of the brazilian punishing sistem to recover and rejain socialize again the delinquent, to disencourage the activity of those potentially faced (turned) to the crime and, at last to punish those who commited a crime -, only punishment is effective. There is a process of negation (denial) of the citizenhood that leads the convict to total alienation of himself, occurrring, in many cases, a phenomenon called imprisonment, which induces to passivity Sand immobilism. Those who are note affected by imprisonment, react. creating a parallel system of power, which is permeated by the creation of a peculiar code, which starts to develop a system of creation, use and dissemination of the information in consideration of the creation of a kind of concept of citizenhood in prison.